Estudio de los musgos epífitos (Bryophyta) presentes en el sendero quishuar del área recreacional el boliche, parque nacional Cotopaxi, Ecuador. - Guamaní Valenzuela, Yolanda Rocío (2020)
This project was carried out with the purpose of briologically inventing the Quishuar path of the Recreational Area in Boliche, Cotopaxi National Park, Cotopaxi Province, Ecuador. Additionally, information was collected regarding the current state of knowledge of the musical flora of the Cotopaxi province. For them, two fundamental sources of information on mosses from Ecuador were reviewed, such as www.tropicos.org and Herbarium of the Pontifical Catholic University of Ecuador (QCA), in total 233 samples from the Cotopaxi province were reviewed; This Cotopaxenses muscular flora is taxonomically divided into: 36 family, 114 genus and 212 species. From this analysis we conclude that the dominant families are: Pottiaceae with: (22 genera / 39 species), Bryaceae (12 genera / 23 species) and Bartramiaceae (8 genera / 18 species). From the results of the inventory of epiphytic mosses of the Quishuar trail, we registered 57 specimens which are distributed in 11 families and 13 genera, these being: Breutelia (Bartramiaceae), Brachythecium (Brachytheciaceae), Calymperes (Calymperaceae): Cryphaea (Cryphaeaceae), Campylopus (Dicranaceae), Hypnum, Mittenothamnium (Hypnaceae): Neckera (Neckeraceae): Orthotrichum (Orthotrichaceae), Prionodon (Prionodontaceae), Pterogonidium, Sematophyllum (Sematophyllaceae) and Porotrichum (Thamnobryaceae). In conclusion, we can indicate that the flora of the province is scarcely inventoried, with the Latacunga canton being the region with the most reports of the brioflora, this work represents the first report of the epiphytic mosses of this recreational area.